GMO Regulations, International Trade and the Imperialism of Standards - Mauro Vigani; Valentina Raimondi; Alessandro Olper (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
This paper deals with the quantification of GMO regulations on bilateral trade flows. A composite index of the complexity of such regulations for sixty countries as well as an objective score for six GMO regulatory sub-dimensions has been developed. Using a gravity model, we show how bilateral similarity?in GMO regulations, affect trade flows for the composite index and its components. Results show that bilateral distance in GMO regulations negatively affect trade flows, especially as an effect of labeling policies, approval process and traceability systems. Interesting, the trade reduction effect induced by GMO standards increase by a factor of four when GMO regulations is treated as endogenous to trade flows. This pattern is consistent with an international environment where large importing countries dictate the rules of the game to developing countries.
Keywords: F13; F14; Q13; Q18; Q17; 330; GMO standards; Harmonization; Trade Flow; Gravity Model; Endogeneity; Biotechnisches Produkt; Agraraußenhandel; Außenhandelspolitik; Indexberechnung; Gravitationsmodell; Welt